THE EFFECT OF BIBLIOTHERAPY ON STUDENT SELF-ESTEEM AT TAMBORA ISLAMIC JUNIOR HIGH SCHOOL - Vina Wulan An-Nida; Lailatul Fadilah; Alif Nurul Rosyidah (Poltekkes Kemenkes Banten, 2026)
Background: Self-esteem is an assessment of an individual’s self, either a positive assessment or a negative assessment. One of the therapies that can be done to increase self-esteem is bibliotherapy. Bibliotherapy is a method utilizing literature that can positively influence an individual’s feelings, attitudes, and behaviors. Objective: This study aimed to determine the effect of bibliotherapy on the self-esteem of students at SMP Islam Tambora. Methods: This research design uses a quantitative approach with a Quasy Experiment design with a one group pretest posttest design. Results: The results showed that before the bibliotherapy intervention, the mean was 17.41, while after the bibliotherapy intervention, the mean was 30.59 and the hypothesis test value using the Dependent T Test test was p value = 0,000. (<0,05). Conclusion: Based on the result, it can be concluded that there is a significant effect of bibliotherapy on the self-esteem of student at SMP Islam Tambora.